High [compact disc] - Urban, Keith, 1967- (Capitol Nashville, 2024)
Four-time GRAMMY Award-winner and three-time CMA Entertainer of the Year recipient Keith Urban releases his eleventh studio album on Capitol Nashville Records. The brand-new collection of eleven songs, includes "Go Home W U" (with Lainey Wilson), "Chuck Taylors," and the hit single "Messed Up As Me." It showcases Urban's extraordinary talents as a vocalist, virtuoso guitarist, songwriter, and collaborator.